2009
DOI: 10.1016/j.otohns.2009.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Updated systematic review of tonsillectomy and adenoidectomy for treatment of pediatric obstructive sleep apnea/hypopnea syndrome

Abstract: Contrary to popular belief, meta-analysis of current literature demonstrates that pediatric sleep apnea is often not cured by T&A. Although complete resolution is not achieved in most cases, T&A still offers significant improvements in AHI, making it a valuable first-line treatment for pediatric OSAHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
339
3
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(368 citation statements)
references
References 40 publications
13
339
3
13
Order By: Relevance
“…Rates of PSG "normalization" varied depending on the cut point employed, with 12% of children achieving postoperative OAHI < 1 event/h, 21% with OAHI < 2 events/h, and 48% of the cohort had a postoperative OAHI < 5 events/h. These rates of PSG improvement are substantially lower compared to generally healthy children, 11,21,22 but similar to that observed in obese children and smaller cohorts of children with DS. 15,16 Although the goal of any sleep surgery is to cure OSA, a positive outcome is to convert a child from moderate/severe obstruction to mild.…”
Section: Discussionsupporting
confidence: 74%
“…Rates of PSG "normalization" varied depending on the cut point employed, with 12% of children achieving postoperative OAHI < 1 event/h, 21% with OAHI < 2 events/h, and 48% of the cohort had a postoperative OAHI < 5 events/h. These rates of PSG improvement are substantially lower compared to generally healthy children, 11,21,22 but similar to that observed in obese children and smaller cohorts of children with DS. 15,16 Although the goal of any sleep surgery is to cure OSA, a positive outcome is to convert a child from moderate/severe obstruction to mild.…”
Section: Discussionsupporting
confidence: 74%
“…Literature review a) Nonrandomised, uncontrolled studies which included children who underwent surgical resection of adenoids and/or tonsils with a mean preoperative AHI of 6.4-69.3 episodes·h −1 were reviewed in two meta-analyses [170,171]. After adenotonsillectomy, AHI decreased.…”
Section: 4mentioning
confidence: 99%
“…However, many reports have suggested that 20% to 40% of pediatric OSA patients continue to show OSA after AT. [9][10][11][12] This phenomenon implies that other predisposing factors may be present in patients with pediatric OSA.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…However, many reports have suggested that 20% to 40% of pediatric OSA patients continue to show OSA after AT. [9][10][11][12] This phenomenon implies that other predisposing factors may be present in patients with pediatric OSA.An abnormality of the maxillofacial morphology, especially small mandibular size relative to oropharyngeal soft tissue, has been revealed to play an important role in the development of OSA in adults. 13 Similarly, a small mandible has been reported to be responsible for the familial aggregation of OSA in both adult and pediatric patients.…”
mentioning
confidence: 99%